Understanding the Sexual Violence Reality: A Review of Community Perspectives and Legal Aspects - Supraptiningsih, Umi; Rahmawati, Theadora; Fauzi, M. Makhrus; Mubarok, Faidol (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The importance of analyzing sexual violence, which frequently occurs both in the private sphere and in the public sphere where the law does not reach. This paper addresses three questions: (a) How is the low awareness of sexual violence victims manifested in taking legal action, (b) why do sexual violence victims exhibit low awareness in taking legal action, and (c) what is the impact of this low awareness on the law enforcement process. This study uses a normative juridical and empirical legal research approach, combining a statutory and conceptual approach, as well as qualitative methods aimed at identifying obstacles in law enforcement against sexual violence crimes. The findings indicate a lack of legal awareness among victims in making reports, which is influenced by factors such as power relations, the status/identity of children born from the abuse, closeness to the perpetrator, and societal stereotypes that view victims negatively. Aspects of law enforcement have not yet guaranteed justice, as they are affected by law enforcers' professional ethics and legislation that is insufficiently accommodating those issues. It is hoped that this article will contribute to a reduction in cases of sexual violence and the attainment of social justice.